Helong Language in West Kupang District, Kupang Regency East Nusa Tenggara is Shifting Towards Death - Sudaryano, Gregorius; Budiarsa, Made; Suastra, I Made; Ola, Simon Sabon (e-Journal of Linguistics; Vol 11 No 2 (2017): eJL-July, 2017)
Research on language shift related to social factor is included in sociolinguistic research. This study is to examine the phenomenon of Helong language (HL) shift  in the District of West Kupang, Kupang Regency, East Nusa Tenggara Province. HL shift is a product of language contact and language competition which is characterized by the use of HL by its speakers that is getting lower and switch to another more prestigious one. Therefore, the phenomenon of HL shift was analyzed based on the choice of HL language use in a domain that implies HL maintenance by its speakers among generations.   In order to get the expected data, this study involved 100 respondents consisting groups of 40 parents, 29 adults, and 31 children. The data obtained through data collection techniques were analyzed by using quantitative and qualitative methods. It was conducted based on the attitude of language in the dimensions of language loyalty, language pride, and awareness of language norms in the domains of family, education, customs, neighborhood, government, and religion referring to the level of HL maintenance.   The results showed that the phenomenon of HL shift in the District of West Kupang, Kupang Regency, East Nusa Tenggara Province reflected reducing number of intergenerational Helong native speakers in using their own language. The presence of Indonesian language (IL) intervening the use of language in the domains of education, government, and religion influencing the use of languages in the domains of family and neighborhood. Thus, HL is shifting towards death in the next generations.